Rational secret sharing scheme based on Markov decision - You-liang TIAN; Xue-mei WANG; Lin-fang LIU (Tongxin xuebao)
The reconstruction methods of a rational secret sharing based on the Markov decision was studied.Firstly,a rational secret sharing system model was proposed using the Markov decision process,which included the players set,the states set,the risk preference function,the state transfer function,the return function,etc.The risk preference function was introduced in order to depict the state set and the state transfer function in this model.Secondly,a rational secret sharing scheme was constructed based on the proposed system model,which was able to solve the secret reconstruction problems according to the Markov strategy.Finally,the functional relations of among the discount factor,the return func-tion and the risk preference function was proposed in this scheme.The analysis results show that the proposed model and scheme are rationality and validity.